Implementation Of Zahir Accounting Version 5.1 In PT Berhasil Beruntung Bersama: Implementation Of Zahir Accounting Version 5.1 In PT Berhasil Beruntung Bersama - Nihlatu Sopyani; Sifa Fauziah; Veti Apriana (Jurnal Mantik, 2020)
In the era of very rapid technological development, every store or company has to implement a computerized information system to create a business system that is more effective, efficient, and produces accurate data. PT Berhasil Beruntung Bersama is one company that still uses an accounting data processing system using Microsoft Excel 2010. With this recording system, problems often occur, including sales of merchandise will be more complicated because they have to calculate the cost of goods manually using the method FIFO (First In First Out), often the difference between recording inventory and goods in warehouse, is more difficult in the process of finding the data needed because it is in the form of documents. Responding to these problems, the authors are interested in conducting research on PT Berhasil Beruntung Bersama where the processing of the data the author uses a computer accounting application that is Zahir Accounting Version 5.1. By using Zahir Accounting, it can be easier for employees to record inventory, search for accounting data and save time and place of storage.